"CORPORATE SOCIAL RESPONSIBILITY PRACTICES AND THEIR INFLUENCE ON BRAND LOYALTY AND CUSTOMER TRUST" (CAHIERS MAGELLANES-NS, 2024)
This study explores the influence of Corporate Social Responsibility (CSR) practices on brand loyalty and customer trust within the consumer goods industry. In an increasingly competitive market, CSR initiatives have emerged as a crucial factor in distinguishing brands and fostering a positive corporate image. This paper investigates how various CSR activities, such as environmental sustainability efforts, ethical labour practices, and community engagement, impact consumer perceptions and behaviours. By employing a mixed-methods approach, including surveys and in-depth interviews with consumers, the study aims to provide a comprehensive understanding of the relationship between CSR practices and customer loyalty. The findings suggest that companies engaging in consistent and transparent CSR activities tend to enjoy higher levels of customer trust and loyalty. Additionally, the research highlights the mediating role of perceived authenticity and corporate reputation in this relationship. The study concludes that businesses that effectively integrate CSR into their core operations not only contribute to societal well-being but also benefit from enhanced brand loyalty and customer trust, leading to a sustainable competitive advantage. These insights are particularly relevant for marketers and corporate strategists seeking to leverage CSR for brand differentiation and long-term success.